Biorefinery Localization Using Analytical Hierarchy Process - Razak, Nurul Hanim; Hashim, Haslenda; Yunus, Nor Alafiza; Klemeš, Jiří Jaromír (Italian Association of Chemical Engineering - AIDIC, 2021)
A critical factor in producing economically viable and environmentally sustainable biomass to biofuels supply chains is a strategic biorefinery location. Sustainable biorefinery location is characterized by replacing fossil fuel with biofuels, enhancing cost-effectiveness, environmental issues mitigation, and stimulating socio-economic growth. The optimal biorefinery location selection depends on trade-offs between five different parameters: Feedstock availability, distance, social measures, cost, and emissions. This paper aims to incorporate qualitative criteria and quantitative criteria using Analytic Hierarchy Process (AHP) in selecting the optimal biorefinery location. The model renders the AHP model to prioritize the optimal biorefinery location with the minimum cost and lower environmental impacts. Sensitivity analysis with continuous criteria weight at 20 % changes is performed to check the robustness of the optimal solution obtained from the AHP optimization model. A case study in Johor, Southern Malaysia, is adopted for this research assessment. Optimal biorefinery location at minimal cost and the lowest emissions is identified using Expert Choice v.11.5. The results indicate that the proposed AHP and sensitivity analysis decision-making model could be robustly used to select biorefinery locations with specified criteria. Conclusively, the systematic methodology presented can help facility planning authorities formulate viable location strategies for a biorefinery in volatile and complex global decision environments.